Gaya Kepemimpinan Ideal Untuk Generasi Z Pada Lingkungan Organisasi - Aquina Tiara Dewi; Kanaya Meidy Andrena; Catharina Aprilia Hellyani (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Leadership style is a characteristic of the behavior of a leader who guides, motivates, guides and directs a group of people or an organization. Generation Z has a leadership style that is not the same as previous generations. This research was conducted to analyze the appropriate leadership style for Generation Z to apply to an organizational environment, this leadership style is a transformational leadership style. The method used is literature study. The results of the study show that a transformative leadership style is the ideal leadership style for Generation Z.